Fundamental Insights from a Single‐Crystal Sodium Iridate Battery. Issue 10 (6th February 2020) - Tepavcevic, Sanja; Zheng, Hong; Hinks, David G.; Key, Baris; Ward, Logan; Lu, Zhi; Stoumpos, Costas; Ren, Yang; Freeland, John W.; Wolverton, Christopher; Phillips, Patrick; Klie, Robert; et al.
Abstract: Electrochemically driven chemical transformations play the key role in controlling storage of energy in chemical bonds and subsequent conversion to power electric vehicles and consumer electronics. The promise of coupling anionic oxygen redox with cationic redox to achieve a substantial increase in capacities has inspired research in a wide range of electrode materials. A key challenge is that these studies have focused on polycrystalline materials, where it is hard to perform precise structural determinations, especially related to the location of light atoms. Here a different approach is utilized and a highly ordered single crystal, Na2− x IrO3 is harnessed, to explore the role of defects and structural transformations in layered transition metal oxide materials on redox‐activity, capacity, reversibility, and stability. Within a combined experimental and theoretical framework, it is demonstrated that 1) it is possible to cycle Na2− x IrO3, offering proof of principle for single‐crystal based batteries 2) structural phase transitions coincide with Ir 4+ /Ir 5+ redox couple with no evident contribution from anionic redox 3) strong irreversibility and capacity fade observed during cycling correlates with the Na + migration resulting in progressive growth of an electrochemically inert O3‐type NaIrO3 phase. Abstract : This work demonstrates for the first time that it is possible to cycle single crystals of Na2− x IrO3 in organic environments, offering a proof‐of‐principle demonstration of single‐crystal based oxide batteries. Cycling of these materials in organic environments enables atomic‐level understanding of the structural and electronic transformations that govern the electrochemical response, confirming that the value of exploring single‐crystalline materials goes well beyond fundamental curiosity.